Test and measurement [Technology 2000 analysis and forecast]. - Bretz, E.A (IEEE spectrum)
The awareness that every electronic product, from PCs to Internet appliances, is pining for tinier and more powerful chips is whipping semiconductor development along at a frenetic pace. It is also hounding automation of design and test and IC test development, but test inevitably lags behind chip development. Devising (and performing) tests for the so-called system on a chip is a time-consuming process. Many thousands of test patterns and vectors must be created, as must protocols, and the fault coverage achieved must be high enough to complete the necessary testing and to minimize the cost. The challenges multiply further as the test chain ascends from chip to board to system and ultimately field-level tests. Each level adds expense so that soon, by some estimates, test could account for half of the final cost of a chip